The Folk Belief and Cultural Heritage in the Syncretic Theravada Buddhism : The Cases of Human-Spirits Relationship in Indonesia, Cambodia and Myanmar - Fuji Riang Prastowo (FKIP, Universitas Palangka Raya, 2023)
This sociological study of religion attempts to explain the relationship between humans and spirits in the syncretism of Theravada Buddhism tradition with case studies in Indonesia, Cambodia, and Myanmar. In these countries, before the influence of the Indian Dharmic Religion, people practiced Theravada Buddhism side by side with folk beliefs. This study uses the theory of correlational theology from Paul Tillich as the search for common ground in reflection of the syncretic folk belief of worshipping Danghyang among Javanese people in Indonesia, Neak Ta among Khmer people in Cambodia, and Nat among Burmese people in Myanmar. The method used literature research and field observations in three countries in 2020. The results of this study are in the exploration of doctrinal concepts from religious texts and the acculturation practices on cultural heritage between the folk belief with the view of wholeness theology in Theravada Buddhism cosmology. Humans live in harmony with other creatures in this world according to the law of attachment and reciprocity, or Paticcasamuppada, consisting of 31 realms of existence. In the context of the three countries, these spirits articulate three relations: the relationship between guardian spirits and the people, the relationship between the deceased spirits and the living, and the relationship between spirits and the social environment, as in line with spiritual ecology (215 words)